Intergroup contact throughout the lifespan modulates implicit racial biases across perceivers' racial group. - Jennifer T Kubota; Jaelyn Peiso; Kori Marcum; Jasmin Cloutier (PLoS ONE, 2017)
Few researchers have investigated how contact across the lifespan influences racial bias and whether diversity of contact is beneficial regardless of the race of the perceiver. This research aims to address these gaps in the literature with a focus on how diversity in childhood and current contact shapes implicit racial bias across perceivers' racial group. In two investigations, participants completed an Implicit Association Test and a self-report measure of the racial diversity of their current and childhood contact. In both studies, increased contact with Black compared with White individuals, both in childhood (Study 2) and currently (Studies 1 and 2), was associated with reduced implicit pro-White racial bias. For Black individuals (Study 2) more contact with Black compared with White individuals also was associated with reduced implicit pro-White racial bias. These findings suggest that diversity in contact across the lifespan may be related to reductions in implicit racial biases and that this relationship may generalize across racial groups.